Debt and PRSP conditionality: The Kenya case - Jane Kiringai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The Kenyan economy had a growth of –0.3 per cent in the year 2001, the lowest growth in the post-independence era. The dismal growth performance coincided with the period when the government was involved in grassroot consultations with civil society and other stakeholders, to find out the causes of poverty and what the stakeholders perceive as the best steps towards poverty reduction, culminating the poverty reduction strategy paper, PRSP. The main argument advanced in this paper is that unless donors are willing to fund poverty programmes unconditionally, there is no scope for funding from domestic resources before the domestic debt problem is addressed. Under the circumstances, the PRSP only enhances stakeholders' expectations, but cannot deliver. The paper concludes that implementing a PRSP would only be effective after the high debt burden is resolved, structural and institutional weakness addressed and significant growth achieved. – debt ; poverty ; fiscal strategy ; external aid
Keywords: F34; H63; O23; O55; 330; Armutspolitik; Auslandsverschuldung; Internationale Kreditvergabe; Kenia